Eosinophilic esophagitis in children: A multicenter study evaluating current practices in Mexico - Victor Gonzalez-Uribe, MD, MSc; Luis A. Hernandez-Zarate, MD; Cesar F. Pozo Beltran, MD; Christian R. Alcocer-Arreguin, MD; Paola de Baro Alvarez, MD, MEd; Natalia Coello-Niembro, MD; Pablo Jimenez-Feria, MD; Zaira S. Mojica Gonzalez, MD; Carlos Andres Gomez-Nuñez, MD; Ricardo Martinez-Tenopala, MD; Martín R. Basile-Alvarez, MD; Berenice Velasco-Benhumea, MD; et al. (Journal of Allergy and Clinical Immunology: Global)
Background: Eosinophilic esophagitis (EoE) is a chronic immune-mediated condition characterized by eosinophil infiltration in the esophagus, leading to symptoms such as food impaction and growth delays. Despite its increasing recognition, there is significant variability in diagnostic and treatment practices, particularly in pediatric populations. Objectives: This study aimed to evaluate the current diagnostic and treatment practices for EoE in children across multiple centers in Mexico, identify common clinical presentations, and assess the role of IgG4 in EoE. Methods: A retrospective analysis was conducted on 32 pediatric patients diagnosed with EoE. Data on clinical symptoms, endoscopic findings, histologic analysis, allergy assessments, and treatment approaches were collected. The presence of IgG4-positive plasma cells was also evaluated. Results: The median age was 10.6 years, with a diagnostic delay of 15.5 months. Acute food impaction was the most common symptom, and 82% had a personal history of atopy. Endoscopic abnormalities were observed in 71% of patients. Histologic analysis confirmed EoE in 83.8% of biopsy samples, with eosinophil counts averaging 17 to 24 per high-power field. IgG4-positive plasma cells were present in 76.5% of patients. Treatment varied, with many receiving proton pump inhibitors and topical corticosteroids, but patients treated with dupilumab showed significant improvement. Conclusions: The study highlights the challenges in diagnosing and managing EoE in children, emphasizing the need for standardized practices and comprehensive evaluations. The presence of IgG4-positive plasma cells suggests a potential role in EoE pathophysiology. Further research is needed to establish effective treatment guidelines and confirm the potential of dupilumab as a therapeutic option.